QTL analysis of cocoon shell weight identifies BmRPL18 associated with silk protein synthesis in silkworm by pooling sequencing. Issue 1 (December 2017) - Li, Chunlin; Tong, Xiaoling; Zuo, Weidong; Luan, Yue; Gao, Rui; Han, Minjin; Xiong, Gao; Gai, Tingting; Hu, Hai; Dai, Fangyin; Lu, Cheng
Abstract Mechanisms that regulate silk protein synthesis provide the basis for silkworm variety breeding and silk gland bioreactor optimization. Here, using the pooling sequencing-based methodology, we deciphered the genetic basis for the varied silk production in different silkworm strains. We identified 8 SNPs, with 6 on chromosome 11 and 1 each on chromosomes 22 and 23, that were linked with silk production. After conducting an association analysis between gene expression pattern, silk gland development and cocoon shell weight (CSW), BMGN011620 was found to be regulating silk production.BMGN011620 encodes the 60S ribosomal protein, L18, which is an indispensable component of the 60S ribosomal subunit; therefore we named itBmRPL18 . Moreover, the clustering of linked SNPs on chromosome 11 and the analysis of differentially expressed genes reported in previous Omics studies indicated that the genes regulating silk protein synthesis may exhibit a clustering distribution in the silkworm genome. These results collectively advance our understanding of the regulation of silk production, including the role of ribosomal proteins and the clustered distribution of genes involved in silk protein synthesis.